1987
DOI: 10.1111/j.1432-1033.1987.tb13520.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of amino acid transport system N in primary cultures of rat hepatocytes

Abstract: The transport of histidine and glutamine via system N in cultured hepatocytes was found to be subject to hormonal control. This long-term regulation showed the following characteristics.1. The transport capacity for histidine and glutamine (system N) increased slowly in response to the combination of dexamethasone and insulin to about 4-fold that of controls after 18-30 h. A similar time course was found for the stimulation of system N (2.5-fold) by dexamethasone and glucagon. In contrast the uptake of a-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…A potential mechanism for increased glutamine transport after RYGB is the pancreatic hormone glucagon. Glucagon has been shown to increase intestinal glutamine transport severalfold (7). Previous studies have shown glucagon levels are increased after RYGB in both patients and the obese ZR model (14,17).…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism for increased glutamine transport after RYGB is the pancreatic hormone glucagon. Glucagon has been shown to increase intestinal glutamine transport severalfold (7). Previous studies have shown glucagon levels are increased after RYGB in both patients and the obese ZR model (14,17).…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocytes isolated from rats treated in vivo with IL-1, the rate of alanine uptake (systems A and ASC) was significantly increased over that seen in hepatocytes from control animals ( 16). TNF administration may also be accompanied by the release of hormonal mediators, such as glucagon and the glucocorticoid hormones, that are known to stimulate system A and system N (8,10,34). Thus, these other cytokines may work together with hormones, such as the glucocorticoids, in an orchestrated fashion to control amino acid transport across the hepatocyte plasma membrane during critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…An amino acid response element regulating the promoter activity has been demonstrated for SAT2 (Palii et al, 2004), whereas a pH responsive element that has been identified in the 3Ј untranslated region of SN1 increases protein expression during acidosis (Solbu et al, 2005). However, reports showing pronounced effects on V max without changing K m for the system A and/or N activities indicate recruitment of transporters from preexisting intracellular pools (Gebhardt and Kleemann, 1987;Hundal et al, 1987;Lohmann et al, 1998;Ling et al, 2001;Pastor-Anglada et al, 2005). Membrane trafficking constitutes a major regulatory pathway for many transporters, including transporters for dopamine, serotonin, GABA, and glutamate, and is often governed by phosphorylation/dephosphorylation of specific residues on the transporter proteins (for review, see Robinson, 2002;Melikian, 2004).…”
Section: Introductionmentioning
confidence: 96%